The Route from Green H2 Production through Bioethanol Reforming to CO2 Catalytic Conversion: A Review - Eugenio Meloni; Marco Martino; Giuseppina Iervolino; Concetta Ruocco; Simona Renda; Giovanni Festa; Vincenzo Palma (Energies, 2022)
Currently, a progressively different approach to the generation of power and the production of fuels for the automotive sector as well as for domestic applications is being taken. As a result, research on the feasibility of applying renewable energy sources to the present energy scenario has been progressively growing, aiming to reduce greenhouse gas emissions. Following more than one approach, the integration of renewables mainly involves the utilization of biomass-derived raw material and the combination of power generated via clean sources with conventional power generation systems. The aim of this review article is to provide a satisfactory overview of the most recent progress in the catalysis of hydrogen production through sustainable reforming and CO2 utilization. In particular, attention is focused on the route that, starting from bioethanol reforming for H2 production, leads to the use of the produced CO2 for different purposes and by means of different catalytic processes, passing through the water–gas shift stage. The newest approaches reported in the literature are reviewed, showing that it is possible to successfully produce “green” and sustainable hydrogen, which can represent a power storage technology, and its utilization is a strategy for the integration of renewables into the power generation scenario. Moreover, this hydrogen may be used for CO2 catalytic conversion to hydrocarbons, thus giving CO2 added value.